2020
DOI: 10.1002/pon.5525
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial distress among oncology patients in the safety net

Abstract: Objective: Psychosocial distress among cancer patients leads to poor health outcomes and lower satisfaction. However, little is known about psychosocial distress among disadvantaged populations. We examined the prevalence, predictors, and follow-up experience of psychosocial distress among cancer patients within a diverse, urban, and multilingual safety-net setting. Methods: We conducted a retrospective cohort study of cancer patients undergoing psychosocial distress screening at initial medical oncology visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…This study was not conducted in the safety-net setting, however, and the sample was 82% White and 60% had commercial insurance. Cimino et al 22 assessed a mixeddiagnosis sample of patients in a safety-net setting at the initial medical oncology visit and found that 61% had clinically significant distress. That study used the NCCN Distress Thermometer, which is known to reflect symptoms of anxiety and depression as well as other aspects of distress, including spiritual, physical, and social problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was not conducted in the safety-net setting, however, and the sample was 82% White and 60% had commercial insurance. Cimino et al 22 assessed a mixeddiagnosis sample of patients in a safety-net setting at the initial medical oncology visit and found that 61% had clinically significant distress. That study used the NCCN Distress Thermometer, which is known to reflect symptoms of anxiety and depression as well as other aspects of distress, including spiritual, physical, and social problems.…”
Section: Discussionmentioning
confidence: 99%
“…We identified only one published study quantifying psychological distress in this population. Cimino et al 22 used the NCCN Distress Thermometer (as opposed to measuring depression and anxiety) and found that 61% of patients with cancer in a safety-net setting endorsed clinically significant distress at their initial medical oncology visit.…”
Section: Introductionmentioning
confidence: 99%
“…This cutoff was chosen based on prior studies showing optimal sensitivity and specificity when a cutoff score of 4 is used. [19][20][21][22][23] Cancer October 15, 2021 Categorical data were compared using nonparametric 2-sided tests, including the Mann-Whitney U test and the Fisher exact test. Univariate and multivariate logistic regression as well as multinomial logistic regression analyses were performed to identify factors associated with ER visits, inpatient hospital admissions, and interruptions to the recommended care plan.…”
Section: Methodsmentioning
confidence: 99%
“…This psychological support should be provided as soon as the disease has been diagnosed, since a cancer diagnosis produces emotional distress in patients and their families [ 1 , 2 , 3 , 4 , 5 ]. Depending on the study, the incidence of clinically significant distress could range between 24% [ 6 ], 52% [ 7 ] and 61% [ 8 ]. These differences may be explained by variations in the specific type of cancer and/or whether patients were assessed at diagnosis or while receiving oncological treatment.…”
Section: Introductionmentioning
confidence: 99%